(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Robert Frost, one of America’s most influential poets, is our job. Frost was known as America’s most influential poet of nature. Frost was born in 1874 and died in 1963 in San Francisco, California.Nature was cherished by Robert Frost. His poem was full of emotion about his personal life and actions. His poems are, however, plain and deep. He has often written basic tales of daily citizens, mostly rural New England residents. Robert Frost wrote a prose with a clear and uncomplicated vocabulary. His poetry involve symbolism, secret messages, sonority, rhyme, meter, metaphors and more. In this review, we explored Robert frost Poetry’s themed approaches.